Effect of Condensed Tannins containing Guava Leaf Meal on Feed intake, Feed Conversion Ratio, Carcass Characteristics and Economics of Broiler Chicks - Daing, M. I.; Pathak, Anand Kumar; Sharma, R. K.; Zargar, M. A. (Indian Journal of Animal Nutrition, 2020)
Present study was undertaken in 120 day-old unsexed broiler chicks. They were randomlydistributed into 4 dietary treatments (T1, T2, T3 and T4 supplemented with guava leaf meal (GLM) @ 0, 1, 2 and 4 % of diet, respectively) of 30 birds per group, each having 3 replicates (10 birds per replicate) in a complete randomized block design (CRD) to evaluate the effect of condensed tannins (CT) containing guava leaf meal (GLM) supplementation on feed intake, feed conversion ratio (FCR), carcass characteristics and economics of broiler chicks. Cumulative feed intake in 0-3, 0-6 and 4-6 weeks of broiler chicks were significantly (P<0.05) higher in T1 followed by T2, T3 and lowest in T4 groups. FCR of 0-3 weeks among groups was found to be statistically non significant (P<0.05), whereas, at 0-6 weeks better FCR was observed in T3 followed by T4 and poor FCR obtained in T1 and T2. Similarly 4-6 weeks FCR was significantly better in T3 followed by T4, T2 while, lower FCR was recorded in T1. GLM incorporation did not exert any adverse effect on carcass characteristics, even though, significantly decreased abdominal fat content and improved lymphoid organ weight. GLM supplementation significantly (P<0.000) increased net profit (Rs.) per bird and benefit: cost ratio in T2, T3 and T4 groups as compared to T1 group. It was concluded that GLM supplementation (1-4%) improved weight gain, FCR and reduced feed intake and could be a better alternative in terms of producing healthy low fat broiler meat.